Categorical assessment and characterization of conventional and unconventional biomass resources in Bangladesh - Hossen, Md Mosaddek; Rahman, AHM Sazedur; Kabir, Afsana Sara; Hasan, MM Faruque; Ahmed, Shoeb (Chemical Engineering Research Bulletin, 2015)
With the rapid industrial growth, the need for renewable energy sources is rising fast. Being a developing country, Bangladesh aims towards industrial expansion, which is always followed by increased energy consumption. Considering the fact that fossil fuel is not sustainable and biomass sources are abundant and offer more versatility, the latter have become an attractive alternative to petroleum-based products. Moreover, utilization of biomass also seems promising because of biodegradability and lower greenhouse gas emissions, ensuring reduced environmental pollution, a grave concern with fossil-fuel technology. Biomass can range from agricultural byproducts to industrial and municipal wastes, however, very few biomass sources are currently being used in Bangladesh. Moreover, biomass can also be utilized to derive valuable chemicals, which are potential raw materials in several existing industries in Bangladesh. Despite having massive potential in Bangladesh, there haven't been organized studies on feedstock types, quantities, characterization and applications. Here we present an organized study to identify potential biomass sources and their available quantities. Considering specific waste fractions from varying sources, total amount of utilizable biomass resources have been calculated. A categorized proximate analysis data summary of varying biomass is also prepared that can be consulted in the future studies to calculate the theoretical possible production of energy as well as useful bio-chemicals based on efficient bio-processing techniques. This work is intended to benchmark the current efforts, and would add valuable information resources for the ongoing research towards achieving energy-sustainability and energy-security in Bangladesh. DOI: http://dx.doi.org/10.3329/cerb.v17i1.22910 Chemical Engineering Research Bulletin 17(2015) 1-10